ARSITEKTUR SISTEM INFORMASI MENGGUNAKAN ENTERPRISE ARCHITECTURE PLANNING - Komarudin, Oman; Fauzi, Ahmad; Ridha, Azhari Ali (Majalah Ilmiah SOLUSI, 2011)
Utilization of information technology to support the activities of the organization has become a necessity in order to enhance the competitive value in the business world. In the utilization of technology and information systems, it is required a plan that includes a blueprint and roadmap for implementation of information systems run smoothly and get maximum results. One method to create this plan is Enterprise Architecture Planning. Before creating the architecture planning, the first step is performing the initial setting that establishes the scope and objectives of planning, then performed the study of the business models and information systems which are already in use in organizations; including the utilization of existing information technology. The next stage is creating enterprise architecture planning includes the data architecture planning, the application architecture planning, and the technology architecture planning that will be implemented in the organization. At the end of this enterprise architecture planning, an implementation plan will be created so the implementation of information systems in organizations can be run continuously and in accordance with the needs that have been analyzed. Case studies conducted at the University of Singaperbangsa Karawang which is an organization of service with a fairly complete business functions as an enterprise. The result of this research is an enterprise architecture model that can be used as the initial step in the development of information systems at the University of Singaperbangsa Karawang so that policies in the development of information systems becomes measurable and clear. Keywords: planning, information system, blue print, roadmap, Enterprise Architecture Planning